2011
DOI: 10.1007/s10346-011-0308-2
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall thresholds for the forecasting of landslide occurrence at regional scale

Abstract: This paper concerns a regional scale warning system for landslides that relies on a decisional algorithm based on the comparison between rainfall recordings and statistically defined thresholds. The latter were based on the total amount of rainfall, which was cumulated considering different time intervals: 1-, 2-and 3-day cumulates took into account the critical rainfall influencing shallow movements, whilst a variable time interval cumulate (up to 240 days) was used to consider the triggering of deep-seated l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
219
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(233 citation statements)
references
References 19 publications
0
219
0
1
Order By: Relevance
“…While this type of methodology might in all probability be less responsive in cases of landslides generally characterized by steady movements (e.g., soil creep, slow mudflows and earthflows), its use may rather be of particular advantage in the case of landslides with a behavior driven for the most part by rainfall intensity, like in the Montescaglioso case study. The dependence between water and slope movements surely recurs frequently in most of the Apennines and in many regions worldwide as well (Canuti et al 1985;Guzzetti et al 2002Guzzetti et al , 2007Martelloni et al 2012;Rosi et al 2012;Segoni et al 2014). On the other hand, a long time series is essential in order to determine representative mean and standard deviation of the incremental displacements.…”
Section: Discussionmentioning
confidence: 99%
“…While this type of methodology might in all probability be less responsive in cases of landslides generally characterized by steady movements (e.g., soil creep, slow mudflows and earthflows), its use may rather be of particular advantage in the case of landslides with a behavior driven for the most part by rainfall intensity, like in the Montescaglioso case study. The dependence between water and slope movements surely recurs frequently in most of the Apennines and in many regions worldwide as well (Canuti et al 1985;Guzzetti et al 2002Guzzetti et al , 2007Martelloni et al 2012;Rosi et al 2012;Segoni et al 2014). On the other hand, a long time series is essential in order to determine representative mean and standard deviation of the incremental displacements.…”
Section: Discussionmentioning
confidence: 99%
“…20 Different numbers of days have been considered and examined by researchers to find the most suitable correlation with landslide initiation (Aleotti, 2004;Polemio and Sdao, 1999;ZĂȘzere et al, 2005). Of the issue, the researchers have proposed different numbers of days, however, only with local validity, which means that suggested rainfall thresholds are applicable to the respective study cases, and it also depends on the landside type (Jakob et al, 2006;Martelloni et al, 2012). Therefore, we referred to the domestic research results in that characteristics of local geology, soil and vegetation, as well as precipitation 25 patterns are different from the areas of other studies.…”
Section: Rainfall Threshold Triggering Landslidementioning
confidence: 99%
“…Despite the limitation on the accumulated landslide inventory data over the study region, the frequency of landslide occurrence was estimated by establishing a rainfall threshold. The selection of the rainfall threshold has been examined and proposed by various methodologies (Crozier, 2005;Guzzetti et al, 2007;ZĂȘzere et 25 al., 2005;Frattini et al, 2009;Crosta and Frattini, 2003;Aleotti, 2004;Polemio and Sdao, 1999;Caine, 1980), and it has been shown that proposed rainfall thresholds are applicable to the respective study cases depending on the landside type with local validity (Jakob et al, 2006;Martelloni et al, 2012), so the criteria of cumulative precipitation and daily rainfall intensity for rainfall threshold setting were determined by referring to the local research results.…”
Section: Introduction 25mentioning
confidence: 99%
“…In WP 3 the research activities include the development of a physically-based model, called HIRESSS Mercogliano et al 2013), for the real time prediction of shallow landslides induced by rain on large areas, predictive statistical models (SIGMA and MACUMBA models) (Martelloni et al 2012;Lagomarsino et al 2013;Segoni et al 2014a, b;Rosi et al 2016) based on the identification of rainfall thresholds for triggering landslides, and a nowcasting system which includes a forecasting and alert system valid at the national level for landslides with fast kinematics (not monitorable by satellite).…”
Section: Wcoe (2014-2017) Activities Research Activitiesmentioning
confidence: 99%